2009
DOI: 10.2500/ajra.2009.23.3366
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mucosal Healing and Infection Associated with Staphylococcus Aureus After Endoscopic Sinus Surgery

Abstract: S. aureus infection at ESS predicts for abnormal, S. aureus-associated mucosal healing and infection post-ESS. Although a prospective trial is warranted, these findings suggest a future role for aggressive anti-S. aureus therapy peri- and/or postoperatively in patients who culture positive for this organism to improve postsurgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 16 publications
6
66
0
Order By: Relevance
“…When the microbial density was compared for these three organisms between CRS and control patients, S. aureus was present at approximately 10 times higher genomes per sample in CRS patients, whereas S. epidermidis and P. acnes were found in similar abundance between both patient groups. The increased bioburden of S. aureus in the disease group is of particular interest, as it is emerging as a prominent disease modifying organism in CRS and it’s presence in patients has important clinical implications [14,15]. The capacity of S. aureus to exist within dense mucosal biofilms has been documented [11,16], which may explain the variable detection from clinical specimens using traditional culture techniques.…”
Section: Discussionmentioning
confidence: 99%
“…When the microbial density was compared for these three organisms between CRS and control patients, S. aureus was present at approximately 10 times higher genomes per sample in CRS patients, whereas S. epidermidis and P. acnes were found in similar abundance between both patient groups. The increased bioburden of S. aureus in the disease group is of particular interest, as it is emerging as a prominent disease modifying organism in CRS and it’s presence in patients has important clinical implications [14,15]. The capacity of S. aureus to exist within dense mucosal biofilms has been documented [11,16], which may explain the variable detection from clinical specimens using traditional culture techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the isolation of S. aureus biofilms in the sinuses of patients with chronic rhinosinusitis (CRS) has been linked to poorer clinical outcomes and disease prognosis[10][12], further defining the importance of this microorganism in disease severity. Although antibiotics initially improve patients’ signs and symptoms, recurrence after treatment cessation is often the case, demonstrating the limitations of the use of antimicrobial compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although in this study we did not examine postoperative outcomes, other studies have looked at the course of patients with persistent bacterial infections postsurgery. Jervis-Bardy et al 6 have shown that the intraoperative presence of S. aureus with failure to clear the bacteria postoperatively leads to persistent mucosal disease at the 90-day postoperative visit. This study suggests that the presence of S. aureus at the time of ESS and the lack of clearance of the bacteria during surgery may be a predictor for surgical failure.…”
Section: Discussionmentioning
confidence: 99%